Systematic Literature Review dan Meta-Synthesis: Fenomena dan Problematika Guru Pendidikan Khusus Non-Pendidikan Luar Biasa - Asma Hanifah; Mohammad Efendi; Ranti Novianti (Jurnal ORTOPEDAGOGIA, 2025)
This Systematic Literature Review research aims to analyze the phenomenon of Special Education Teachers who’s not graduated from Special Education study program that happened working at inclusive and special schools and the problems they face. The method used is a meta-synthesis with a meta-aggregation approach. These teachers are present because of the lack of educators with special education qualifications; the lack of interest in special education study programs; the lack of universities that have special education majors; graduates from the special education program tend to choose to work in special school rather than in inclusive schools because of better job status; and these special education teachers are eventually recruited from class teachers/subject teachers who do not have special education backgrounds, as well as from individuals who are trained about special education to become special education teacher. Due to the lack of knowledge about children with special needs. They face difficulty in understanding the characteristics of and interacting with children with special needs; experience high levels of stress and do not have good emotional regulation; have low self-efficacy and lack confidence in teaching; and their performance and services provided to students with special needs are less than optimal.